Who are the most highly cited forensic scientists in the United States?. Issue 3 (16th March 2023) - Jones, Alan Wayne
Abstract: The most highly cited forensic practitioners in the United States were identified using a publicly available citation database that used six different citation metrics to calculate each person's composite citation score. The publication and citation data were gleaned from Elsevier's SCOPUS database, which contained information about 7 million scientist each of whom had at least five entries in the database. Each individual was categorized into 22 scientific fields and 176 subfields, one of which was legal and forensic medicine (LFM). The database contained citation records for 13, 388 individuals having LFM as their primary research discipline and 282 of these (2%) were classified as being highly cited. Another 99 individuals in the database had LFM as their secondary discipline, making a total of 381 highly cited forensic practitioners from 35 different countries. The career‐long publication records of each individual were compared using their composite citation scores. Of the 381 highly cited scientists, 93 (24%) had an address somewhere in the United States. The various branches of forensics they specialized in were anthropology, criminalistics, DNA/genetics, odontology, pathology, statistics/epidemiology, and toxicology. The two most highly cited scientists, according to their composite citation score, were both specialists in DNA/genetics. Bibliometric methods are widely used for evaluating research performance in academia and a similar approach might be useful in jurisprudence, such as when an expert witness is instructed to testify in court and explain the meaning of scientific evidence.